Morphological comparison of Astropecten cingulatus and a new species of Astropecten (Paxillosida, Astropectinidae) from the Gulf of Mexico - Lawrence, John M.; Cobb, Janessa C.; Herrera, Joan C.; Durán-González, Alicia; Solís-Marín, Francisco Alonso (Zootaxa, 2018)
Astropecten cingulatus is a conspicuous species, which displays a large superomarginal plate series on the abactinal surface. Herein we describe a new species from off the Texas coast that shows the superficial appearance of A. cingulatus, including these large superomarginal plates, but with armature differing from that of typological A. cingulatus. This species shows the actinal surface of the inferomarginal plates without the squamules present on A. cingulatus. In addition, the adambulacral plates possessed but a single central large spine surrounded by a circle of spines rather than spine rows. The abactinal paxillar region was also very narrow. Statistical analysis of these and other morphological characters showed the specimens differed significantly from those of A. cingulatus. The regression of the slope of R:SM# vs. R was significant but the intercept was not. Therefore the two species are indistinguishable at small sizes based on R:SM. Compared to known Atlantic Astropecten spp. these observed characters warrant the description of a new species, Astropecten karankawai, for the specimens from off the coasts of Texas and Mexico.